Severe soft tissue injuries in multiple trauma patients—a challenge we can meet? A matched-pair analysis from the TraumaRegister DGU® - Nora Kirsten; Georg Maximilian Franke; Rolf Lefering; Tim Klüter; Matthias Weuster; Michael Müller; Sebastian Lippross; Andreas Seekamp; TraumaRegister DGU®; Stefanie Fitschen-Oestern (Frontiers in Medicine)
IntroductionDespite tremendous clinical efforts over the past few decades, the treatment of severely injured patients remains still challenging. Concomitant soft tissue injuries represent a particular challenge, as they can lead to complications at any time of trauma care, hold a high risk of infection and often require multiple surgical interventions and interdisciplinary collaboration.MethodsThis retrospective, multicentric study used the TraumaRegister DGU® to examine the effect of open fractures and severe soft tissue injuries on outcome of multiple trauma patients. Primary admitted multiple trauma patients at the age of 16 to 70 years, treated from 2010 to 2021, were included. A Matched pair analysis was performed for better comparability of trauma patients with and without open fractures and/or severe soft tissue injuries.ResultsAfter applying the matching criteria, 5,795 pairs were created and analyzed. The group with sustained soft tissue injuries/open fractures was found to have a higher ISS ([mean ± SD] 22.1 ± 10.4 vs. 20.6 ± 10.2, p < 0.001). Endotracheal tube insertion (27.7% vs. 30.4%, p = 0.003), catecholamine administration (6.0% vs. 8.4%, p < 0.001) and cardio-pulmonary resuscitation (1.6% vs. 2.1%, p = 0.027) were more frequent in the group with sustained soft tissue injury. Both groups were equally frequent admitted to the intensive care unit (ICU) and length of stay (LOS) at the ICU (median (quartiles) 3 (1–9) versus 3 (1–9)) did not differ significantly. However, total LOS at the hospital was longer for the group with sustained soft tissue injury (median (quartiles) 18 (11–29) versus 17 (10–27)). Sepsis occurred more often in patients with soft tissue injury (4.3% vs. 5.2%, p = 0.034). There was no significant difference in prevalence of multi organ failure, 24 h-mortality (2.1% vs. 2.5%, p = 0.151) and overall-mortality (3.6% vs. 3.9%, p = 0.329) between both groups.ConclusionDue to database analysis and revision of guidelines, the treatment of severely injured patients has steadily improved in recent years. Patients with severe soft tissue injuries/open fractures required more medical interventions and length of stay at the hospital was longer. In this study, we were able to show that although concomitant severe soft tissue injuries required more ICU interventions and led to a longer length of stay, 24-h and all-cause mortality were not significantly increased.